Rural transformation, inequality, and the origins of microfinance - Marvin Suesse; Nikolaus Wolf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
What determines the development of rural financial markets? Starting from a simple theoretical framework, we derive the factors shaping the market entry of rural microfinance institutions across time and space. We provide empirical evidence for these determinants using the expansion of credit cooperatives in the 236 eastern counties of Prussia between 1852 and 1913. This setting is attractive as it provides a free market benchmark scenario without public ownership, subsidization, or direct regulatory intervention. Furthermore, we exploit features of our historical set-up to identify causal effects. The results show that declining agricultural staple prices, as a feature of structural transformation, leads to the emergence of credit cooperatives. Similarly, declining bank lending rates contribute to their rise. Low asset sizes and land inequality inhibit the regional spread of cooperatives, while ethnic heterogeneity has ambiguous effects. We also offer empirical evidence suggesting that credit cooperatives accelerated rural transformation by diversifying farm outputs.
Keywords: 330; microfinance; credit cooperatives; rural transformation; land inequality; Prussia